Impact of oxidation and carbonation on the release rates of iodine, selenium, technetium, and nitrogen from a cementitious waste form - Chen, Zhiliang; Zhang, Peng; Brown, Kevin G.; van der Sloot, Hans A.; Meeussen, Johannes C.L.; Garrabrants, Andrew C.; Wang, Xinyue; Delapp, Rossane C.; Kosson, David S. (Journal of hazardous materials, 2023)
Evaluation of the long-term retention mechanisms and potential release rates for the primary constituents of potential concern (COPCs) (i.e., Tc, I, Se, and nitrate) is necessary to determine if Cast Stone, a radioactive waste form, can meet performance objectives under near-surface disposal scenarios. Herein, a mineral and parameter set accounting for the solubility of I and Se in Cast Stone was developed based on pH-dependent and monolithic diffusion leaching test results, to extend a geochemical speciation model previously developed. The impact of oxidation and carbonation as environmental aging processes on the retention properties of Cast Stone for primary COPCs was systematically estimated. Physically, the effective diffusion coefficients of 4 COPCs in Cast Stone were increased after carbonation and/or oxidation, reflecting an increase in permeability to diffusion. Chemically, i) pH & pe conditions in the original Cast Stone were favorable for the stabilization of Tc, but not for I, Se, and N; ii) oxidation (with/without carbonation) of Cast Stone changed the pe & pH conditions to be detrimental for Tc stabilization; and iii) carbonation (with/without oxidation) of Cast Stone modified the pH & pe conditions to be beneficial for the stabilization of I (in system with Ag added) and Se. [Display omitted] •Precipitates and parameters accounting for the solubility of I and Se are postulated.•Cast Stone carbonation decreased pH, which was chemically beneficial for Se retention.•Effective diffusivity of ions in Cast Stone was increased by carbonation and/or oxidation.•Ag-based getter was effective to stabilize I under oxic and near neutral conditions.